Cyclic analysis and capacity prediction of concrete filled steel box columns. - Susantha, K.A.S.
Concrete filled steel columns have been widely used in civil and architectural constructions throughout the world in recent years. This study is concerned with the cyclic elastoplastic analysis and capacity prediction of concrete filled steel columns having thick and thin walled stiffened box shaped sections. An analytical procedure for determining the ultimate state of the concrete filled steel column is proposed based on the fiber analysis technique. Strength and ductility predictions are made by means of a new failure criterion. This is proposed based on the average failure strain of concrete and steel at critical regions. A recently developed monotonic stress strain relation for confined concrete is modified so that it can be uesd in the analysis of thin or thick walled section columns with stiffeners. A simple cyclic rule is introduced into this model in order to be used in cyclic analysis. Material non-linearity of steel is represented by the modified two surface model developed at Nagoya University. The predictions are then compared with the existing experimental results and found to exhibit satisfactory agreement. Both small and large scaled columns are considered in the comparisons.
Keywords: Concrete filled steel column; Confinement; Uniaxial concrete model; Ductility; Ultimate strength; Cyclic analysis